De philautia breviter expendens - Sundwall, Johannes; Mellenius, Abrahamus; Frenckell, Johan Christopher II (kirjapaino, Turku, 1785-1814); Turun Akatemia; Royal Academy of Turku; Regia Academia Aboensis; Kungliga akademin i Åbo (Aboae : typis Frenckellianis, [1787], 1787)
Invokaatio: D.F.G.
Keywords: moraali